2008
DOI: 10.1371/journal.ppat.1000141
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide-3 Kinase-Akt Pathway Controls Cellular Entry of Ebola Virus

Abstract: The phosphoinositide-3 kinase (PI3K) pathway regulates diverse cellular activities related to cell growth, migration, survival, and vesicular trafficking. It is known that Ebola virus requires endocytosis to establish an infection. However, the cellular signals that mediate this uptake were unknown for Ebola virus as well as many other viruses. Here, the involvement of PI3K in Ebola virus entry was studied. A novel and critical role of the PI3K signaling pathway was demonstrated in cell entry of Zaire Ebola vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

22
177
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(200 citation statements)
references
References 54 publications
22
177
1
Order By: Relevance
“…It is only its endosomal release into the cytoplasm that requires an endosomolytic agent such as perforin (29,32). Various viruses are known to carry molecules with such properties to enable their endocytic entry into the cytoplasm after cellular uptake (29,(33)(34)(35). Consequently, a series of studies have shown that virus particles can enable a cytotoxic effect of GrB in the absence of perforin (29,36).…”
Section: Discussionmentioning
confidence: 99%
“…It is only its endosomal release into the cytoplasm that requires an endosomolytic agent such as perforin (29,32). Various viruses are known to carry molecules with such properties to enable their endocytic entry into the cytoplasm after cellular uptake (29,(33)(34)(35). Consequently, a series of studies have shown that virus particles can enable a cytotoxic effect of GrB in the absence of perforin (29,36).…”
Section: Discussionmentioning
confidence: 99%
“…As viruses can manipulate or make use of the cytoskeletal network of actin filaments during their life cycles, (virus-induced) Rac1 activity has been linked to viral infection or protein trafficking processes as well as the spread of several viruses causing severe human diseases, for example, HIV (Lu et al, 1996), Ebola (Saeed et al, 2008), HSV-1 (Hoppe et al, 2006), HBV (Gros et al, 2008) and paramyxoviruses, for example, Hendra virus (Schowalter et al, 2006). From rodent experiments Rac1 is known to have oncogenic activity and to be involved in tumorigenesis (Kissil et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Many viruses exploit the PI3K/Akt pathway to facilitate various steps in their replication cycle, such as regulation of gene expression and genome replication. However, our study does not rule out the possibility that inhibition of PI3K/Akt activation blocks entry of PCV2 into host cells, as described for Ebola virus (45), thereby reducing viral DNA replication and viral protein synthesis and causing lower production of infectious virus particles in the PCV2-infected cells. (20 M).…”
Section: Discussionmentioning
confidence: 69%
“…1C); virus receptor attachment and/or cell entry might be required for PI3K/Akt activation in the PCV2-infected cells, as described for some other viruses (28,29,40,64). During their entry into cells, adenovirus, adenovirus-associated virus, respiratory syncytial virus, and Ebola virus all have the ability to promote PI3K/Akt signaling without expression of viral products (28,29,35,40,45,64). Also, the PI3K/Akt pathway is simultaneously induced by intracellular viral proteins and particle adhesion during the internalization process of some viruses, including human papillomavirus (17), influenza A virus (14), respiratory syncytial virus (30), and bovine herpesvirus type 1 (66).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation